2014
DOI: 10.1080/15546128.2014.976353
|View full text |Cite
|
Sign up to set email alerts
|

Is Texting Ruining Intimacy? Exploring Perceptions Among Sexuality Students in Higher Education

Abstract: In the context of researchers' and educators' concerns about the pervasive use of technology to communicate with one another, this study explored whether the frequency of emerging adults' computermediated communication (CMC) is correlated with their perceptions of intimacy, relationship, and sexual satisfaction. The sample included 298 young adults ages 18-29, primarily female students in human sexuality courses, who had been in a face-to-face romantic relationship for at least six weeks and who used CMC to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
(26 reference statements)
0
1
0
1
Order By: Relevance
“…Because of the ambiguity of messages communicated electronically, we might expect relational problems to arise in relationships with heavy electronic communication usage. However, one recent study found no significant correlation between frequency of CMC (in this case referring to texting, instant messaging, and e-mail) and sexual satisfaction among young adults (McGee, 2014). In fact, the author argued that CMC usage may actually help some couples manage their relationship.…”
Section: Channelmentioning
confidence: 96%
“…Because of the ambiguity of messages communicated electronically, we might expect relational problems to arise in relationships with heavy electronic communication usage. However, one recent study found no significant correlation between frequency of CMC (in this case referring to texting, instant messaging, and e-mail) and sexual satisfaction among young adults (McGee, 2014). In fact, the author argued that CMC usage may actually help some couples manage their relationship.…”
Section: Channelmentioning
confidence: 96%
“…468-469), on peut se demander de quelle façon les textos -un moyen de communication a priori plus limité que la communication en faceà-face ou même le téléphone pour la transmission de signaux non verbaux -affectent les relations amoureuses. Même s'il est toujours ardu de déterminer si l'utilisation de nouveaux moyens de communication est généralement bénéfique ou nuisible aux relations interpersonnelles (Hwang, 2011;McGee, 2014), le présent article cherche à faire la lumière sur la question en se penchant plus spécifiquement sur l'utilisation des textos entre partenaires amoureux.…”
Section: Introductionunclassified